The Relationship Between Reef Fish and Coverage of Coral and Turf Algae in Coral Reef Ecosystems of Biak Island, Papua - Aji, Ludi Parwadani; Putra, Risandi Dwirama; Abrar, Muhammad; Siringoringo, Rikoh Manogar; Giyanto, Giyanto (UI Scholars Hub, 2025)
In this study, we examine the influence of benthic coverage on fish diversity in coral reef ecosystems. Benthic and reef fish community surveys were conducted at 14 sites using underwater photographic transect and underwater visual census methods, respectively. Coral cover (26.1%) was found to be lower than turf algae cover (42.1%). A total of 56 fish species, comprised of 14 carnivores, 21 corallivores, and 21 herbivores, were recorded. The most widely distributed carnivore and herbivore species were Lethrinus harak and Ctenochaetus striatus, respectively. Two species of butterflyfish, Chaetodon citrinellus and Chaetodon trifasciatus, were the most widely distributed species among corallivores. The number of herbivorous fish species was correlated with coral cover, but not turf algae cover. In contrast, no correlation was observed between the diversity of corallivorous and carnivorous fish and the coverage values of the two benthic groups (coral and turf algae). Despite this, a pattern was observed in which areas with higher coral cover had more corallivorous and carnivorous fish species, while sites with higher turf algae cover had fewer of these fish species. Reef fish distribution depends on live coral, which are the primary habitat-forming organisms on coral reefs. Coral and reef fish are essential in maintaining ecological functions and shaping reef ecosystems.